Coping Strategies with Genito-Pelvic Pain/Penetration Disorder: A Qualitative Study - Mojdeh Banaei; Vahid Mehrnoush; Nasibeh Roozbeh; Nourossadat Kariman (Pain Research and Management)
Background. Genital/pelvic pain penetration disorder (GPPPD) decreased mental and physical functioning, reduced quality of life, and reduced feelings of inadequacy and worthlessness, all of which impair the ability of women with GPPPD to enjoy sex. This qualitative study was conducted to identify which factors can reduce sexual stress and help Iranian women cope with GPPPD. Methods. This qualitative study was conducted through the participation of 18 women with GPPPD diagnosed by a sexologist and using DSM-IV diagnostic criteria from March to July 2022, Iran. The samples were selected using the purposive sampling method and considering the maximum variation. The semistructured question guide was used as a data collection tool and data collection continued until data saturation was reached. The collected data were analyzed using conventional content analysis approach. Results. Data analysis led to the emergence of three main themes: “problem-focused coping” which included the three categories of received social support, problem self-control, and penetration replacement; “emotion-focused coping” which included three categories: a couple’s negative reaction to the problem, attachment disorder, and surrendering the problem; and “treatment-seeking” which consisted of searching and choosing a therapist to solve the problem, ineffective medical approaches, and ineffective nonmedical approaches. Conclusion. Coping strategies in women with GPPPD were classified as “problem-focused coping,” “emotion-focused coping,” and “treatment-seeking.” These findings indicate a need for GPPPD information and education, as well as a need for healthcare professionals to actively inquire about sexual problems and commit to serious treatment efforts. Cultural interventions that promote sexual pleasure can aid in the management of GPPPD.